REACTIVE FLOW FEATURE ON SOFTWARE-DEFINED NETWORKING ARCHITECTURE USING OPENDAYLIGHT CONTROLLER - Lingga, Patrick
This final work is the development of the application that is called Easy Flow. The Easy Flow application was the result of my senior final work. Petra Febrianto Liasta, Radifan Cahya Pradana, and Fandi Rusdiantara were the one who made the application. Easy Flow is a web application that implements Software-Defined Networking that uses the OpenFlow protocol. A new feature is developed for Easy Flow. The feature is called reactive flow. Some challenges were found when developing the reactive flow application. The development was first started using Java programming language for OpenDaylight controller. But it quickly ended because it is necessary to understand OpenDaylight and Java to use them properly. As the author does not have enough experience in OpenDaylight and Java, it will take a long time to learn both of them. This problem caused the need for alternative solutions to be able to develop the application quicker. The alternative solution is to use the REST API. This is a better solution because it is easier to use and will not take a long time to learn. The purpose of this final work is to develop Easy Flow by providing an additional method, namely reactive flow and designing the flow needed for reactive flow so this method can be used on layer 2 and layer 3 network communication. The method is carried out step by step starting from the study of literature, designing the flow for communication, designing reactive flow application, and testing the application. Literature studies are conducted by studying the previous final work and online sites. Flow is made using the basic theory that has been obtained before. The application is made using Python programming language and tested on the mininet network simulator. The results from the reactive flow testing are the application work successfully used in mininet network simulator. By using this application, the switch can work automatically without the user need to configure the flow. The advantage of this application is that it will make the switch can communicate layer 2 and layer 3 networks. But this application requires several features on the switch so that not all switch hardware can be used for the application. Therefore, further research is needed so the applications can be used for all of the switches in the network.